Hypoplastic Left Heart Syndrome: Prognostic Significance of Morphological Variants of the Heart in the Choice of Treatment Approach - Zakharova, V.; Savchuk, T.; Truba, Ya.; Lazoryshynets, V.; Rudenko, O. (Ukrainian Journal of Cardiovascular Surgery, 2021)
Hypoplastic left heart syndrome (HLHS) is one of the most complicated congenital heart defects which leads to the inevitable fatal outcome in the natural course of the disease. Currently, Norwood procedure and fetal aortic valvuloplasty are considered the major approaches for surgical treatment of HLHS. However, the prognosis of such surgeries is often unpredictable. The aim. To study morphological variations of the left ventricle (LV) in HLHS and evaluate the prognostic significance of each of them in the choice of surgical approach. Materials. The main group included 63 hearts of newborns with HLHS, the comparison group included 53 hearts of newborns without cardiac pathology. Methods. The methods used were survey microscopy, as well as macro- and micromorphometry of various parameters of the heart, calculation of the ratio of their absolute values (indices) with subsequent statistical data processing. Results. Five types of LV were identified in HLHS patients based on the size and shape of the cavity, wall thickness, presence or absence of fibroelastosis: slit-like hypoplastic (Type I) (n = 10; 15.9%); slit-like hypertrophic (Type II) (n = 19; 30.2%); cylindrical (Type III) (n = 22; 34.9%); lacunar (Type IV) (n = 6; 9.5% ); lacunar-cylindrical (Type V) (n = 6; 9.5%). In Type I left ventricles, the interventricular index (IVI) (the ratio of the areas of the free walls of the left and right ventricles on the cross sections of the heart) was the smallest: 0.13 ± 0.03 units versus normal 1.96 ± 0.31 units. In Type II left ventricles, the value was equal to 1.69 ± 0.23 units; in Type III it was 1.59 ± 0.64 units; in Type IV it was 1.31 ± 0.03 units; in Type V it was 1.05 ± 0.52 units. The index of the working area of the right ventricular myocardium (RVI) (the ratio of the area of the free wall of the right ventricle to the sum of the areas of the free wall and interventricular septum) in Type I LV was the highest: 81.3 ± 5.7% versus normal 57.1 ± 2.02%; in Type II it was 49.7 ± 6.4%; in Type III it was 39.8 ± 2.9%; in Type IV it was 69.7 ± 16.1%; in Type V it was 41.3 ± 24.4%.Type III–V LVs have always been associated with fibroelastosis, in contrast to Type I and II LVs. Conclusions. In HLHS, Type I hearts are the most eligible for the Norwood procedure, since the LV, due to its minimal size, is not an excess ballast for the working right ventricle. Type II LV is optimal for the fetal aortic valvuloplasty, since during the II-III trimesters of gestation they can join the circulatory system due to remodeling. HLHS with LV fibroelastosis (Types III, IV, V) seem to be the least favorable for both pre- and postnatal surgery, especially in the presence of fibroelastosis of the right ventricle.